Is unwilling volunteering protective for functional decline? The interactive effects of volunteer willingness and engagement on health in a 3‐year longitudinal study of Japanese older adults. Issue 7 (16th April 2019) - Nonaka, Kumiko; Fujiwara, Yoshinori; Watanabe, Shuichiro; Ishizaki, Tatsuro; Iwasa, Hajime; Amano, Hidenori; Yoshida, Yuko; Kobayashi, Erika; Sakurai, Ryota; Suzuki, Hiroyuki; Kumagai, Shu; Shinkai, Shoji; et al.
Abstract : Aim: The present study explored the interactive effects of willingness to volunteer and actual volunteer engagement on the maintenance of functional health among older Japanese adults, using data from a 3‐year longitudinal study. Methods: We used data from the 3‐year longitudinal Tokyo Metropolitan Institute of Gerontology Longitudinal Interdisciplinary Study on Aging (1997). We examined 676 older adults aged >65 years from the rural Nangai District who were independent in their basic activities of daily living (BADL). A follow‐up study was carried out in 2000. We categorized participants into four groups: "willing volunteers, " "unwilling volunteers, " "willing non‐volunteers" and "unwilling non‐volunteers." Logistic regression analyses were carried out to evaluate the interactive effects of willingness to volunteer and actual engagement in volunteering at baseline on BADL decline over a 3‐year period. Results: During the follow‐up period, 6.6% of willing volunteers, 17.4% of unwilling volunteers, 16.3% of willing non‐volunteers and 21.0% of unwilling non‐volunteers experienced a decline in BADL. Unwilling volunteers (odds ratio [OR] 2.88, 95% confidence interval [CI] 1.29–6.43) and both non‐volunteer groups (willing: OR 2.70, 95% CI 1.28–5.72; unwilling: OR 2.48, 95% CI 1.32–4.64) had significantly higher odds of BADL decline than did willing volunteers. When unwilling non‐volunteer was set as the reference, the OR of unwilling volunteers became 1.16 (95% CI 0.55–2.49), suggesting that unwilling volunteers had a similar odds of BADL decline as non‐volunteers. Conclusion: Volunteer activity is effective for preventing BADL decline only for those who willingly engage.Geriatr Gerontol Int 2019; 19: 673–678 .